Repatriation policy of the Republic of Kazakhstan: to the issue of the causes of the Kazakhs return (International relations and international law Journal, 2016)
In the early 1990s, repatriation of Kazakhs to their historical homeland has been declared as a priority of the migration policy of the Republic of Kazakhstan . Program of resettlement of returnees was specially developed , also a system of quotas was introduced. Immigrants are known as « oralmans « . Since 2008 , the program of resettlement of ethnic Kazakhs has been carried out under the name of «Nurly Kosh» . Peak repatriation was in the middle of the 1990s. Since gaining independence, about one million ethnic Kazakhs migrated to Republic of Kazakhstan. Mostly migrate from countries such as: Russia , Mongolia , China , Kyrgyzstan , Uzbekistan , Turkmenistan , Iran, Turkey, India , Pakistan, Afghanistan, etc. Purpose of the article is to examine the reasons for the repatriation of Kazakhs to their historical homeland. The scientific approach involves the study of the issue from a theoretical point of view. Used two paradigms of international relations theory : liberalism and constructivism .
Keywords: repatriation of Kazakhs; oralman; liberalism and constructivism theories in study of repatriation program